Electroencephalography, Magnetic Resonance Imaging and Response to Treatment in Children with Focal Seizures A Prospective Cohort Study: Nejad Biglari et al., Focal-onset Seizures - Nejad Biglari, Habibe; Molaeifarsangi, Mohammadhosein; Ahmadipour, Habibeh; Eftekhar Vaghefi, Rana; Shafie'ei, Mohammad; Parvaresh, Saeedeh (Iranian Journal of Child Neurology, 2023)
Objectives This study aimed to evaluate patients with focal seizures, their clinical manifestations, and their response to treatment, then compared the accuracy of electroencephalography and Magnetic Resonance Imaging (MRI) to assess the cost-effectiveness of the latter. Materials & Methods After selecting the appropriate individuals, the authors obtained the data by clinically evaluating the cases and interviewing them or their caretaker(s) on admission and the six-month follow-up visit. The researchers then analyzed the obtained data. Results Most cases (88.4%) had idiopathic seizures. A positive family history of seizures was observed in eight cases (5.4%). Respectively, theoccipital, frontal, and temporal lobes showed the highest frequencyo normalities on electroencephalography, while periventricular leukomalacia was the highest abnormal MRI finding (4.1%). However, in 87.8% of cases, this modality’s results were normal. No recurrence of seizures was observed in 116 cases (78.9%) on the sixmonth follow-up visit, pointing towards an appropriate response to treatment. Conclusion While this study revealed that most had normal MRI, reporting an abnormality in electroencephalography was a more prevalent occurrence. This finding undermines the cost-effectiveness of the former modality, even though its importance in diagnosing the underlying abnormalities necessitates further studies regarding the subject at hand. Furthermore, the study of age groups showed that treatment response is less desirable in children under two years of age, suggesting more intense workups.